The external forces acting in the direction of travel and their relation to mechanical energy dissipation in slalom - Gilgien, M.; Reid, R.; Haugen, P.; Smith, G. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The literature quantifying the external forces acting on an alpine skier is limited in general, but particularly in the slalom discipline. This study therefore describes the size and time course of the external forces acting on a skier parallel to the direction of travel based on the kinematics of a group of highly skilled slalom racers. Subsequently, the braking forces of ski-snow friction and wind drag are related to mechanical energy dissipation. Method: The derivation of the external forces was based on the kinematics of 6 members of the Norwegian Europa Cup team (aged 17-20). Skier kinematics were captured during 2 turns of a slalom race simulation by 4 panning and synchronized camcorders [1]. The centre of mass (COM) position calculation was based on the Zatsiorsky body segment parameter model and the de Leva adjustments. The component of gravity accelerating the skier downhill and the resultant force were both calculated from the COM position data. To calculate the air drag force, frontal area was estimated using a kinematics-based procedure, drag coefficients were adapted from a study of cross country skiers [2], and COM velocity was calculated using finite central differences. The remaining frictional force in the ski snow interaction was calculated as the difference between the resultant force, the air drag force and the component of gravity accelerating the skier downhill. Skier mechanical energy dissipation, defined as the amount of total mechanical energy dissipated to the surroundings per meter altitude skied [3], was derived from the COM position data. The braking forces were then correlated to mechanical energy dissipation. Results: The air drag force acting in slalom is rather small and constant (25 - 50N), while the frictional force between ski and snow alters rapidly during a turn cycle with peak values as high as 500N occurring at about gate passage. Energy dissipation showed a strong inverse statistical correlation with the frictional force in the ski-snow interaction (R2 = -0.96, p < 0.001), while the relation between energy dissipation and the air drag force was not significant.